Unraveling Hydra bioelectrical activity on multielectrode array - Blasio, Martina; Zenna, Claudia; Intartaglia, Daniela; Tommasini, Giuseppina; Coppola, Giuseppe; Granata, Federica; Tino, Angela; Santillo, Silvia; Tortiglione, Claudia (Frontiers in Bioengineering and Biotechnology, 2026)
Introduction: Multielectrode array (MEA) technology has emerged as a powerful tool for extracellular recording of electrical activity across a wide range of experimental models, from single cells to organoids. Advanced devices have been developed to monitor and stimulate microscale biological systems enabling precise interrogation of cellular networks and tissue-level electrophysiology. Although these technologies generated promising results, they are not yet widely accessible to neuroscientists and neurobiologists due to limitations in adapting MEAs for whole-organism recordings, in maintaining stable tissue-electrode interfaces, and in decoding the complexity and diversity of bioelectrical signals of intact organisms. Methods: In this study, we demonstrate the feasibility of recording the bioelectrical activity from a whole millimeter-sized organism (Hydra vulgaris) using a commercially available multielectrode recording system. Additionally, we introduce a custom MATLAB-based algorithm designed for comprehensive analysis and comparison of small animal model extracellular signals.Results: Two distinct recording configurations were evaluated, each differing in the extent of tissue-electrode coupling area and resulting in variations of the recorded bioelectrical pattern. Discussion: Our findings underline the strict dependency of the recordings from the device architecture and highlight the potential of Hydra as a versatile model in bioelectronics, with applications ranging from the development and validation of advanced microengineered devices to fundamental studies on neuronal circuits and neuromodulation.